Outside Front Cover: Biotechnology Journal 5/2020. Issue 5 (28th April 2020) - Koudan, Elizaveta V.; Gryadunova, Anna A.; Karalkin, Pavel A.; Korneva, Janetta V.; Meteleva, Nina Y.; Babichenko, Igor I.; Volkov, Aleksey V.; Rodionov, Sergey A.; Parfenov, Vladislav A.; Pereira, Frederico D. A. S.; Khesuani, Yusef D.; Mironov, Vladimir A.; et al.
Abstract : Tissue spheroids (TS) represent a building block in biofabrication. In this study, authors suggest a procedure for systematic multiparametric characterization of TS to generate viable cell aggregates with defined morphology, biomechanical properties and uniform predictable geometry from different types of cells. The cover image represents this process as an automated production line equipped with different tools. This is reported by Elizaveta V. Koudan, Anna A. Gryadunova, Pavel A. Karalkin, Janetta V. Korneva, Nina Y. Meteleva, Igor I. Babichenko, Aleksey V. Volkov, Sergey A. Rodionov, Vladislav A. Parfenov, Frederico D. A. S. Pereira, Yusef D. Khesuani, Vladimir A. Mironov, Elena A. Bulanova in article 1900217 .